2016
DOI: 10.5796/electrochemistry.84.797
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrode Performance of Li<sub>4</sub>MoO<sub>5</sub>-LiFeO<sub>2</sub> Binary System as Positive Electrode Materials for Rechargeable Lithium Batteries

Abstract: A binary system, x Li 4 MoO 5 -(1 − x) LiFeO 2 , is studied as electrode materials for rechargeable lithium batteries. A sample of single phase is obtained at x = 0.5, and it is found that Li 1.42 Mo 0.29 Fe 0.29 O 2 (x = 0.5) crystalizes into Li 5 ReO 6 -type structure. Although an initial charge capacity of Li 1.42 Mo 0.29 Fe 0.29 O 2 reaches 350 mAh g −1 , irreversible phase transition associated with oxygen loss and molybdenum migration on charge is evidenced by X-ray diffraction and X-ray absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…There were no visible spectral features in the Mo M-edge. We expect Mo to remain largely as Mo 6+ (as previously observed for LN20) 9, 17 , though a small amount of oxygen loss during the first charge may allow for some Mo reduction near the surface of LNF15 particles upon subsequent discharge 9, 29 . The F K-edge spectra are not presented due to the strong but non-relevant contribution from the PTFE binder.…”
Section: Resultssupporting
confidence: 57%
“…There were no visible spectral features in the Mo M-edge. We expect Mo to remain largely as Mo 6+ (as previously observed for LN20) 9, 17 , though a small amount of oxygen loss during the first charge may allow for some Mo reduction near the surface of LNF15 particles upon subsequent discharge 9, 29 . The F K-edge spectra are not presented due to the strong but non-relevant contribution from the PTFE binder.…”
Section: Resultssupporting
confidence: 57%
“…37) and Li 1.42 Mo 0.29 Fe 0.29 O 2 (ref. 38). Similar to Li 1.3− x Nb 0.3 Fe 0.4 O 2 clear evidence for the formation of superoxide and large polarization on charge/discharge have been reported for both samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a binary system, x Li 4 MoO 5 −(1− x ) LiFeO 2 , is studied as electrode materials for rechargeable lithium batteries . A sample of single phase is obtained at x =0.5, and it is found that Li 1.42 Mo 0.29 Fe 0.29 O 2 ( x =0.5) also crystalizes into Li 5 ReO 6 ‐type structure.…”
Section: Li4moo5 As Host Structure Of Lithium‐excess Compoundsmentioning
confidence: 99%